2012
DOI: 10.1073/pnas.1204158109
|View full text |Cite
|
Sign up to set email alerts
|

Fighting malaria with engineered symbiotic bacteria from vector mosquitoes

Abstract: The most vulnerable stages of Plasmodium development occur in the lumen of the mosquito midgut, a compartment shared with symbiotic bacteria. Here, we describe a strategy that uses symbiotic bacteria to deliver antimalaria effector molecules to the midgut lumen, thus rendering host mosquitoes refractory to malaria infection. The Escherichia coli hemolysin A secretion system was used to promote the secretion of a variety of anti-Plasmodium effector proteins by Pantoea agglomerans, a common mosquito symbiotic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
270
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(275 citation statements)
references
References 40 publications
4
270
0
1
Order By: Relevance
“…Recent studies reported the presence of symbiotic bacteria, such as Pantoea agglomerans or Asaia in midgut lumen with anti-Plasmodium effector proteins that render host mosquitoes refractory to malaria infection [6,10,13]. Engineered P. agglomerans strains were able to inhibit Plasmodium falciparum development by 98% [13]. Other studies showed that insects with an important microbiota seem more resistant to infections and certain bacteria, such as Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported the presence of symbiotic bacteria, such as Pantoea agglomerans or Asaia in midgut lumen with anti-Plasmodium effector proteins that render host mosquitoes refractory to malaria infection [6,10,13]. Engineered P. agglomerans strains were able to inhibit Plasmodium falciparum development by 98% [13]. Other studies showed that insects with an important microbiota seem more resistant to infections and certain bacteria, such as Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Then, there is a growing interest on bacterial biodiversity in Anopheles mosquitoes and particularly those based on the identification of bacteria to be used for malaria transmission blocking based on bacterial genetic changes to deliver antiparasite molecules or paratransgenic approach [5][6][7][8][9][10][11][12][13]. Recent studies reported the presence of symbiotic bacteria, such as Pantoea agglomerans or Asaia in midgut lumen with anti-Plasmodium effector proteins that render host mosquitoes refractory to malaria infection [6,10,13]. Engineered P. agglomerans strains were able to inhibit Plasmodium falciparum development by 98% [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wolbachia has been shown to inhibit the replication of multiple arboviruses and filarial nematodes within Aedes mosquitoes (27)(28)(29)(30), as well as to shorten the host life span, not permitting cyclical pathogen development and transmission (31). Additionally, symbionts within the guts of mosquitoes and triatome bugs are being genetically modified to produce antiparasitic molecules, in efforts to block transmission of malaria (32) and Chagas disease (33), respectively. Knowledge of tsetse fly symbiosis not only stands to provide basic insight into how microbial partners adapt and respond to changes in ecological factors and parasite infections but may also be of applied value to generate novel modes of pest biocontrol (26).…”
Section: The Tsetse Flymentioning
confidence: 99%
“…gambiae and An. stephensi and successfully suppressed transmission of Plasmodium falciparum and P. berghei, respectively [68].…”
Section: Biological Control Of Pest and Vector Insectsmentioning
confidence: 99%